The Role of E-Commerce in Equitable Digital Economy in Indonesia - Adinugraha, Hendri Hermawan; Sadali, Ayatullah; Rahmawati, Ferida; Andrean, Rizky (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2024)
The rapid development of online trading or e-commerce has become a new phenomenon in the Indonesian economy. This fact has not been proven to impact the welfare of digital economic equality in Indonesia positively. This study intends to explain the role of e-commerce in the distribution of the digital economy in Indonesia. This study uses a systematic literature review method. The data sources for this research come from books, journals, and other literature related to the role of e-commerce in the distribution of the digital economy in Indonesia. The findings in this literature review conclude that, ideally, high e-commerce transactions can benefit the realization of economic equality in Indonesia. This fact can be found in the e-commerce business, which has embraced local economic sectors such as agriculture, plantations, fisheries, and even MSMEs in all regions by playing an active role in this digital-based trade. Technology has been proven to break the long chain in the distribution process. Business actors in rural areas and regional MSMEs can be essential if they can make friends with technological sophistication. Local business actors can increase their productivity and welfare. Support from the Indonesian government is urgently needed to build infrastructure to realize trade through digital media in villages and remote areas. Another tough challenge is ensuring the e-commerce business is fully secure to gain the public’s trust.